Left bundle branch block in diphtheritic myocarditis A case study - A. Samik Wahab, A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Left bundle branch block is very rare in children. A boy, 5 years old with diphtheritic myocarditis had left bundle branch block in ECG pattern during the first days in hospital. He had received basic DPT vaccination 4 1/2 years ago, when his age was three months.The prognosis of left bundle branch block in diphtheritic myocarditis is usually poor. However, as he received DPT vaccination in the last 5 years the prognosis was tending to good. After 11 days hospitalisation, the ECG pattern suddenly reversed to normal. The follow up- through outpatient department has no further complications, despite he discharged with still high LDH serum leveLThe purpose of this study is to report a very rare case, and this case hopefully to be the last diphtheritic disease in Yogyakarta, due to a very good coverage of vaccination.Key Words: diphtheria diphtheritic myocarditis left bundle branch block DPT vaccination LDH enzyme